Optimizing Tugboat Fuel Efficiency at Biringkassi Port: A PLS-SEM Structural Modelling Approach - Filman Genda; Corvis L. Rantererung; Atus Buku (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2026)
This study develops a diagnostic model to evaluate harbor tugboat fuel consumption efficiency at Biringkassi Port, addressing the need to reduce operating costs and greenhouse gas emissions in maritime logistics. Unlike previous studies focusing on deep-sea vessels, this research considers the unique operating characteristics of harbor tugboats. A four-construct framework comprising Ship Operations (X1), Engine and Equipment Performance (X2), Environmental Factors (X3), and Operator Behavior (X4) was evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data from 50 maritime experts and validated operational records were analyzed using SmartPLS 4.0. The results identify Ship Operations as the dominant determinant of fuel consumption efficiency (β = 0.729, p < 0.001), followed by Environmental Factors (β = 0.099), Engine and Equipment Performance (β = 0.087), and Operator Behavior (β = 0.062). The proposed model explains 71.8% of the variance in fuel consumption efficiency (R² = 0.718) and demonstrates strong predictive relevance (Q² = 0.491). The findings indicate that optimizing voyage scheduling and standardizing speed-to-distance ratios can significantly improve fuel efficiency while reducing operating costs and carbon emissions. The proposed framework provides a practical diagnostic tool for port authorities and a scalable basis for future multi-port validation.